Syrian Refugees and Their Impact on Health Service Delivery in the Pediatric Hematology/Oncology Clinics Across Canada. Issue 2 (March 2020) - Barry, Rachid M.; Chretien, Christine; Kirby, Melanie; Gallant, Gloria; Leppington, Sarah; Robitaille, Nancy; Corriveau-Bourque, Catherine; Stoffman, Jayson; Wu, John; Leaker, Michael; Klaassen, Robert J.
Abstract : This study examined the impact of Syrian refugees on 1 area of the Canadian health care sector. We predicted that pediatric hematology clinics across Canada would see a spike in their Syrian refugee patient population in proportion to their recent migration and, as a result, an increase in perceived workload. Data on the number of refugee patients, types of diseases, and perceived workload were gathered from hematology clinics across Canada using a clinical survey (Supplemental Digital Content 1, http://links.lww.com/JPHO/A315 ). The results showed that Ontario had the most Syrian refugee patients, followed by the Quebec, Western Canadian, and Atlantic regions. The results also showed that perceived workload ranged from "no increase" (4 programs) to "minimal increase" <25% (1 program), "moderate increase" 25% to 75% (4 programs), and "significant increase" >75% (3 programs, 2 of which had no transfusion-dependent thalassemia patients before the immigration). Abstract : Supplemental Digital Content is available in the text.